1992
DOI: 10.1099/0022-1317-73-8-1899
|View full text |Cite
|
Sign up to set email alerts
|

Ordered appearance of human immunodeficiency virus type 1 nucleic acids following high multiplicity infection of macrophages

Abstract: The order of appearance of human immunodeficiency virus type 1 (HIV-1) nucleic acids was examined in monocyte-derived macrophages following a high multiplicity infection with macrophage-tropic virus. Using the polymerase chain reaction, viral DNA was first detected 2 h after infection and continued to accumulate over the next 24 h. Transcripts representing tat, rev and nefsplicing were detected by 24 h, and transcripts representing env splicing were detected by 48 h after infection. Coincident with the appeara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
17
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 28 publications
4
17
0
Order By: Relevance
“…We found that HIV-1 1.8-kb mRNA accumulated 12 h earlier in lymphocytes than in MDM. This comparative delay in MDM agrees with the 12-h delay observed in one study of U937 cells (39) but not the 4-h delay reported in another study (32). It also agrees with our previous work in which we found that in fully susceptible MDM, compared to freshly isolated monocytes that are resistant to infection, reverse transcription and integration are detectable by 12 and 24 h postinfection, respectively (52).…”
Section: Discussionsupporting
confidence: 82%
“…We found that HIV-1 1.8-kb mRNA accumulated 12 h earlier in lymphocytes than in MDM. This comparative delay in MDM agrees with the 12-h delay observed in one study of U937 cells (39) but not the 4-h delay reported in another study (32). It also agrees with our previous work in which we found that in fully susceptible MDM, compared to freshly isolated monocytes that are resistant to infection, reverse transcription and integration are detectable by 12 and 24 h postinfection, respectively (52).…”
Section: Discussionsupporting
confidence: 82%
“…4b). These data are consistent with those published by Munis et al (1992), who reported a significant increase of HIV-1 DNA during the first cycle of infection. No PCR products were detected in the MDM infected with heatinactivated virus stock pretreated with RNase-free DNase (data not shown).…”
supporting
confidence: 83%
“…Because both processes were inhibited, inhibition of the former cannot be attributed to the formation of a dead-end complex (22,36). Our results indicate that the mutant polymerase harboring mutations D67N, K70R, T215F, and K219K is either totally unable to unblock the AZT-terminated primer during the initiation of reverse transcription or at least that this process is too slow to be significant during provirus synthesis in vivo (41,42). Thus, if a resistant virus incorporates AZT during this step, its replication is definitively blocked.…”
Section: Discussionmentioning
confidence: 88%